0.058 mm2 13 Gbit/s inductorless analogue equaliser with low-frequency equalisation compensating 15 dB channel loss - Boon, Chirn Chye (2019)
An inductorless 13 Gbit/s analogue equaliser with an additional low-frequency equalisation (LFEQ) to counter the low-frequency channel losses is presented. An active feedback topology for the proposed equaliser together with negative capacitance circuit is used to extend the bandwidth to compensate a 15 dB channel loss at Nyquist. The LFEQ improves the measured data jitter of the conventional equaliser from 0.41 to 0.12 UI, for a pseudorandom binary sequence of 231 - 1. The proposed prototype was implemented in 65 nm CMOS, occupying active area of merely 0.058 mm2. It exhibits a power efficiency of 1.07 mW/Gitb/s under a supply voltage of 1.2 V and a BER < 10-12.